Coherent Laser Beam Combining 2013
DOI: 10.1002/9783527652778.ch01
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Coherently Combined, High‐Power Laser Systems

Abstract: In recent years, much effort has been expended toward scaling electric lasers to CW power levels on the order of 100 kW or greater [1]. The key challenge in such scaling is maintaining near-diffraction-limited (DL) beam quality (BQ) to enable tight focusing onto a distant target. Despite the maturation of scalable, diode-pumped laser amplifier technologies such as zigzag slabs [2] or fibers [3], thermal effects or optical nonlinearities currently limit near-DL output from single lasers to an order of magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…A patented technique [22] allows the distributed antenna aperture to coherently up-convert an incident RF field to the optical domain for passive beam-space processing. This preservation of an incident phase front through the up-conversion process enables beam-space processing of the incident field using free-space interferometry of optical beams [23], [24]. A series of bi-convex lenses take the Fourier transform of the optical field at the input of the free-space optics ("Optical Processor") while distributed Bragg reflector (DBR) filters isolate the first lower sideband of the optical signal generated by the phase modulation of the incident light, while the rejected optical carriers are used to maintain spatial coherence among the array elements as described in [22]- [24]…”
Section: A Overviewmentioning
confidence: 99%
“…A patented technique [22] allows the distributed antenna aperture to coherently up-convert an incident RF field to the optical domain for passive beam-space processing. This preservation of an incident phase front through the up-conversion process enables beam-space processing of the incident field using free-space interferometry of optical beams [23], [24]. A series of bi-convex lenses take the Fourier transform of the optical field at the input of the free-space optics ("Optical Processor") while distributed Bragg reflector (DBR) filters isolate the first lower sideband of the optical signal generated by the phase modulation of the incident light, while the rejected optical carriers are used to maintain spatial coherence among the array elements as described in [22]- [24]…”
Section: A Overviewmentioning
confidence: 99%
“…It requires a proper and stable phase relationship of the sampled gain medium. Different approaches have been demonstrated: active phase locking of amplifiers seeded by a single frequency laser split into several beams or passive phase locking of emitters in an extended cavity [14]. Impressive results for CBC using a limited number of high power fiber amplifiers (P > 100W per channel) show the potential of power scaling by CBC reaching kW level powers [15,16].…”
Section: Coherent Beam Combiningmentioning
confidence: 99%
“…For decades, laser coherent combination has been proved to be an efficient way to combine multiple laser beams together for achieving high power output due to its advantage of maintaining good beam quality. And many studies have demonstrated filling factor [4]- [6] is an important parameter to affect coherent combination efficiency [7]- [9]. To increase beam coherent combination, people need to reduce beams space and increase the filling factor of coherent combination array.…”
Section: Introductionmentioning
confidence: 99%